CADMIUM EXPOSURE ON Donax trunculus (MOLLUSCA BIVALVIA) LETHALITY PARAMETERS AND BIOMARKERS RESPONSES - Belabed, S; Soltani, N. (My University, 2022)
Cadmium is a non-essential heavy metal in the biological system. In this study, we have highlighted to evaluate of the effect toxicity of cadmium chloride (CdCl2) against Marine Bivalve Donax trunculus L. (Mollusca, Bivalvia) under laboratory conditions. The acute bioassay tests at various gradient concentrations of cadmium (5, 7.6, and 10 mg/L) were performed to estimate lethal concentrations 50 (LC50 Concentration estimated that produces a 50% mortality in a test population over a specific period) and 90 (LC90) for 24, 48, 72, and 96 hours of exposure. 96h-LC50 and 96h-LC90 values are: 2.59 and 9.25 mg/L respectively. In addition, the sublethal concentrations (LC10 and LC25) at acute exposure (96 h) which are: 0.72 mg/L and 1.32 mg/L respectively, and their fiducial limits were investigated. The results obtained indicate that cadmium causes mortality in the species studied with a Concentration-response relationship. Thus, specimens of this marine bivalve were experimentally exposed to CdCl2 at concentrations corresponding to 96h-LC10 and 96hLC50, to evaluate the effect of toxicity on catalase (CAT) and acetylcholinesterase (AChE) activities, followed by a recovery period during 4 days. Results showed that Cd inhibited AChE activity suggesting neurotoxicity disturbances. In addition, we observed a stimulation of the detoxification system as shown by an increase in catalase activity. Additionally, the transfer of individuals exposed to CdCl2 in untreated water showed a gradual restoration of the initial state. The data obtained from this study will provide useful information for understanding the toxicological process of CdCl2 in Donax trunculus.